2013
DOI: 10.1158/1078-0432.ccr-13-1442
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II and Biomarker Study of Ramucirumab, a Human Monoclonal Antibody Targeting the VEGF Receptor-2, as First-Line Monotherapy in Patients with Advanced Hepatocellular Cancer

Abstract: Purpose To assess the efficacy and safety of the anti-VEGF receptor-2 (VEGFR-2) antibody ramucirumab as first-line therapy in patients with advanced hepatocellular carcinoma and explore potential circulating biomarkers. Experimental Design Adults with advanced hepatocellular carcinoma and no prior systemic treatment received ramucirumab 8 mg/kg every two weeks until disease progression or limiting toxicity. The primary endpoint was progression-free survival (PFS); secondary endpoints included objective respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 32 publications
8
94
0
1
Order By: Relevance
“…Consistent with multiple prior studies of anti-VEGF/VEGFR agents, including bevacizumab in sarcoma, rectal, breast, and ovarian cancer, we found that anti-VEGF therapy led to a sustained increase in PlGF, suggesting that this may be a pharmacodynamic marker of activity (21)(22)(23)(24)(25)(26)(27)(28). We also found that, although pretreatment plasma VEGF does not associate with outcome, higher levels of sVEGFR1 before combination therapy were associated with worse survival.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with multiple prior studies of anti-VEGF/VEGFR agents, including bevacizumab in sarcoma, rectal, breast, and ovarian cancer, we found that anti-VEGF therapy led to a sustained increase in PlGF, suggesting that this may be a pharmacodynamic marker of activity (21)(22)(23)(24)(25)(26)(27)(28). We also found that, although pretreatment plasma VEGF does not associate with outcome, higher levels of sVEGFR1 before combination therapy were associated with worse survival.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that, although pretreatment plasma VEGF does not associate with outcome, higher levels of sVEGFR1 before combination therapy were associated with worse survival. Multiple previous studies have shown that high levels of sVEGFR1 are correlated with worse clinical outcomes, making sVEGFR1 a potential biomarker of intrinsic resistance to antiangiogenic therapy (22,28). Finally, the number of circulating CD14+ monocytes, a potential biomarker of systemic inflammation, associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients enrolled in this trial have wellpreserved liver function. An interesting aspect in this trial is the observed OS stratified by liver function difference, showing longer OS favoring ramucirumab Child-Pugh B group than Child-Pugh A group (18.0 mo vs 4.4 mo, both are barcelona clinic liver cancer-C) [47] . This positive study spurred the initiation of REACH (NCT01140347).…”
Section: Cediranib (Azd2171) Is Another Multitargeted Inhibitor Of Vementioning
confidence: 93%
“…There is also VEGF gene overexpression (vascular endothelial growth factor) that correlates with the tumor's angiogenic capacity [10] and has led to attempts to develop target therapies against VEGF [11] . Other oncogenic factors include the overexpression of extracellular matrix metalloprotease inducers (EMMPRIN or CD147) that have been associated to increased vascularization, invasion, metastases development and tumor recurrence [12] .…”
Section: Molecular Pathogenesismentioning
confidence: 99%